2013
DOI: 10.1016/j.bcp.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine signaling and progression of chronic kidney disease in smokers

Abstract: The deleterious health effects of cigarette smoking are far reaching, and it remains the most important modifiable risk factor for improving overall morbidity and mortality. In addition to being a risk factor for cancer, cardiovascular disease and lung disease, there is strong evidence, both from human and animal studies, demonstrating a role for cigarette smoking in the progression of chronic kidney disease (CKD). Clinical studies have shown a strong correlation between cigarette smoking and worsening CKD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 114 publications
2
58
2
5
Order By: Relevance
“…21,25 In addition, nicotine binds a range of nicotinic acetylcholine receptors expressed by mesangial, endothelial, vascular smooth muscle, and renal proximal and distal tubule cells. [195][196][197][198] These receptors are expressed under normoxic conditions but are induced by both transient and chronic hypoxia. 199,200 Upon nicotine binding, receptors mediate activation of protein kinase C that in turn activates nicotinamide adenine dinucleotide phosphate-oxidase to produce reactive oxygen species.…”
Section: Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,25 In addition, nicotine binds a range of nicotinic acetylcholine receptors expressed by mesangial, endothelial, vascular smooth muscle, and renal proximal and distal tubule cells. [195][196][197][198] These receptors are expressed under normoxic conditions but are induced by both transient and chronic hypoxia. 199,200 Upon nicotine binding, receptors mediate activation of protein kinase C that in turn activates nicotinamide adenine dinucleotide phosphate-oxidase to produce reactive oxygen species.…”
Section: Hypertensionmentioning
confidence: 99%
“…199,200 Upon nicotine binding, receptors mediate activation of protein kinase C that in turn activates nicotinamide adenine dinucleotide phosphate-oxidase to produce reactive oxygen species. 195,196,[201][202][203][204] Stable compounds within cigarette smoke, such as acrolein, also induce endothelial production of reactive oxygen species through activation of nicotinamide adenine dinucleotide phosphate-oxidase. 205 These oxygen species then act in the same way as those generated through hypertension and hyperglycemia to drive renal hypoxia and kidney damage.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potent evidence showed that human mesangial cells possess the neuronal nicotinic acetylcholine receptors (nAChRs) [26]. The expression of nAChRs subunits promotes the nicotine effect on activating pro-fibrotic pathways, reducing glomerular filtration rate and glomerular filtration rate [27]. Accordingly, response to organic substance is a significant biological process in the development of kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we reported that the anticancer agent 5-aza-cytidine (AZA) elicits oxidative stress-mediated toxicity in cultured renal proximal tubule cells via transcriptional upregulation of the prooxidant p66shc gene and consequent increase in mitochondrial reactive oxygen species (ROS) release (2). Studies revealed that smoking augments severity and progression of renal diseases in humans (3) and in various animal models (4)(5)(6). However, there are no data available on whether smoking could affect renal toxicity of anticancer agents.…”
mentioning
confidence: 99%